"Emmetropic, but not myopic human eyes distinguish positive defocus from calculated defocus in monochromatic red light". (March 2022) - Swiatczak, Barbara; Schaeffel, Frank
Abstract: Studies in animal models have provided evidence that broadband light and chromatic cues are necessary for successful emmetropization. We have studied this question in young human subjects by measuring short-term changes in axial length when they watched movies with calculated defocus (2.5D) or optically defocused movies (+2.5D) with red interference filters (620 ± 10 nm). Since filters cut luminance down by a factor of 10, a control experiment with neutral density filters (ND 1.0) was done. Ten myopes and 10 emmetropes were studied. Four experimental conditions were tested on two separate days. On the first day, movies with calculated defocus, and defocused by positive lenses were watched with ND filters. On the second day, movies with the same defocus patterns were watched with the red filters. Movies were presented on a large TV screen (LG OLED65C9, 65″) in a dark room at 2 m distance for 30 min. Changes in axial length before and after each stimulation were measured with the Lenstar (LS 900, with autopositioning system; Haag-Streit). Interestingly, the effects of calculated defocus or optical positive defocus on axial length were suppressed by 1.0 ND filters in myopes and emmetropes, with no clear trend. In contrast, narrow-band red light suppressed eye elongation with calculated defocus but not eye shortening with positive defocus in emmetropes. In myopes, as previously found in white light, there was a trend of axial eye elongation with positive lenses. In conclusion, the effect of positive lenses on eye growth did not require chromatic cues.